Time-Adjusted Immune Indices: A Circadian Perspective on Neutrophil-to-Lymphocyte Ratio in Immunotherapy - Bivolarski, Ivan (AL-Kindy College Medical Journal, 2025)
Immune indices such as the neutrophil-to-lymphocyte ratio (NLR) are widely used to monitor patients on immune checkpoint inhibitors, yet their interpretation rarely consider time-of-day biology. This perspective proposes a circadian framework in which sampling time and treatment timing shape baseline values, short-term fluctuations, and prognostic thresholds. Drawing on clinical observations across lungs, renal, and other tumors, I outline how morning versus afternoon therapy and corticosteroid administration may differentially modulate NLR trajectories and toxicity and introduce practical steps for time-adjusted reporting: record clock time, analyze intra-patient trends, and compare like-for-like time windows. Integrating chronobiology into routine hematologic